2017
DOI: 10.4274/tybd.04696
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Progressive Muscle Relaxation Exercises After Endotracheal Extubation on Vital Signs and Anxiety Level in Open Heart Surgery Patients

Abstract: Objective: The purpose of this study was to examine the effects of the exercises of progressive muscle relaxation (PMR) on vital signs and anxiety level after endotracheal extubation in open heart surgery. Materials and Methods: This study was carried out as quasi-experimental, pre-test, and post-test with a control group. The study recruited 30 experimental and 30 control group open heart surgery patients, who met the inclusion criteria, from a cardiac and vascular surgery clinic of a university hospital. PMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 22 publications
1
11
0
10
Order By: Relevance
“…A similar study conducted to examine the effect of relaxation therapy revealed significant reduction in systolic and diastolic blood pressure in patients with elevated blood pressure (Soliman & Mohamed, 2013). A recent study conducted to investigate the effect of relaxation technique on vital signs found significant lower rate of pulse, respiration and blood pressure in the experimental group when compared to control group (İbrahimoğlu & Kanan, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…A similar study conducted to examine the effect of relaxation therapy revealed significant reduction in systolic and diastolic blood pressure in patients with elevated blood pressure (Soliman & Mohamed, 2013). A recent study conducted to investigate the effect of relaxation technique on vital signs found significant lower rate of pulse, respiration and blood pressure in the experimental group when compared to control group (İbrahimoğlu & Kanan, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Hemodinamik salah satu parameter respon fisik dan psikologis akibat pengaruh sistem saraf simpatis (15,16,20). Penelitian pada pasien bedah abdomen didapatkan PMR menurunkan nyeri pasca operasi dan terlihat dari hemodinamik pasien pada kelompok intervensi yang lebih rendah dibandingkan kelompok kontrol (15) .…”
Section: Hemodinamikunclassified
“…Dalam penelitian ini didapatkan nyeri pasca operasi abdomen tidak mempunyai korelasi dengan Heart Rate (HR) dan Respiratory Rate (RR) tetapi berhubungan dengan peningkatan mean arterial pressure (MAP) p<0,05. Jurnal Penelitian Kesehatan Suara Forikes ------http://forikes-ejournal.com/index.php/SF Hal ini berbeda dengan penelitian pada pasien bedah jantung terbuka di Turki bahwa penerapan PMR pasca ekstubasi dapat menstabilkan HR, RR, TD, MAP pada grup intervensi dibandingkan dengan grup kontrol (16) . Hal ini sama dengan penelitian lainnya, PMR dan konseling psikologi dapat menurunkan HR dan TD pasien grup intervensi (20) .…”
Section: Hemodinamikunclassified
See 2 more Smart Citations